Climate change and its impact on the health - Ahmad, Muneeb (IIPA Digest)
Today, worldwide, there is an apparent increase in many infectious diseases, which reflects the combined impacts of rapid demographic, environmental, social, technological and other changes in our ways of living. Climate change will affect infectious disease occurrence in humans. It is a known fact that climatic conditions affect epidemic diseases from long before the role of infectious agents was discovered, late in the nineteenth century. Changes in infectious disease transmission patterns are a likely major consequence of climate change. Climate changes include alternations in one or more climate variables including temperature, precipitation, wind, and sunshine. These changes may impact the survival, reproduction or distribution of disease pathogens and hosts, as well as the availability and means of their transmission environment. The health effects of such impacts tend to reveal as shifts in the geographic and seasonal patterns of human infectious diseases and as changes in their outbreak frequency and severity. Climate change is the prime health threat facing humanity and health professionals worldwide. Countries are already responding to the health harms caused by this unfolding disaster. Abundant literature addresses the factorial and potential impacts of climate change on many types of infectious diseases, including vector borne, water-borne, airborne, and food-borne diseases.- Reproduced